Purchasing Behaviour of Young-Adult Consumers for Canned Tuna Products in Kuala Lumpur, Malaysia - Abdullah, Nova Zuhra (2005)
Tuna is practically the only fish processed and traded at an international scale (Josupeit, 2004). The trade has evolved into an enormous international industry. The size and scope of this industry has made it one of the world's most lucrative industries. Malaysia also involved into this industry by being the pioneer in the tuna processing industry in South East Asia in the 1960s, when it formed the Malayan Marine Industry (MMI). However, the markets in the tuna products industry vary according to region and countries, with markedly different types of consumers; each requires a different market approach and adopts certain basic purchase decision making styles. Consumers make purchase decisions based on the learning process, which ultimately affects their buying behaviours. Therefore, understanding consumer decision making styles is essential in the food processing industry, particularly in the lucrative tuna products industry, to maintain competitive advantage. The objectives of the study are to determine decision making styles of young-adult consumer for canned tuna products purchases, to investigate relationship of decision making styles with socio-demographic background and to recommend appropriate strategies of canned tuna marketing to current market situation. The sample sizes of 400 respondents were used for the study. Data were analyzed by descriptive analysis, [actor analysis, t-Test and analysis of variance (ANOVA). Results of the descriptive analysis showed that more than half (77.5%) of the respondents consumed canned tuna products approximately one to three times a month, 17.8% four to six times a month, and 4.8% more than six times a month. Results of factor analysis gave a ten-factor solution but only eight factors were reliable. The eight factors are health consciousness, convenience consciousness, taste focused, brand consciousness, ethical concern, habitual and brand loyalty, familiarity and eating habit, and price equals quality concern. Results of t-test and ANOVA showed that eight socio-demographic variables have relationship on canned tuna products purchase decision making styles, namely gender, age, race, education level, occupation, marital status, residential area and position in family. Income level and size of household do not seem to influence consumer canned tuna products purchase decision making styles. The study proves the existence and difference of young-adult consumer decision making styles of purchasing canned tuna products. Malaysia has the potential to be a player in the largely lucrative tuna products industry, even though the industry has only been a niche market here. By understanding the consumer decision making styles of tuna products consumption, food manufacturers and marketers in Malaysia are able to seriously and meticuloudy approach this industry to gain competitive edge. Certainly, there is an urgent need for developments in the tuna processing industry in Malaysia in terms of fishing gears and methods, production technology, joint venture, training programs, product innovations and market segmentation based on socio-demographic background and consumer life